Effects of Pit-Bottom-Soil Reinforcement on the Deformation of Subway Deep Foundation Pits Based on an Improved Model - Yan Wang; Fei Zhang (Advances in Materials Science and Engineering)
Reinforcement of pit bottom soil has been utilized in subway deep foundation-pit engineering in soft-soil areas. This study proposes an improved foundation-pit excavation model to better investigate the effect of soil reinforcement at the bottom of a pit on the deformation of a subway’s deep foundation pits. The strength parameters of the reinforced soil utilized in the improved model could be obtained through a cone penetration test before and after the pit-bottom-soil reinforcement. The results show that the enveloped structure’s lateral displacement and the surface settlement outside the pit were reduced by 37% and 23% after soil reinforcement, respectively. The uplift suppression in the centre of the base exhibited a significant effect, and the uplift suppression exceeded approximately 50%. Thus, the foundation reinforcement could effectively reduce the subway foundation-pit support structure’s horizontal deformation, ground settlement, and the pit bottom soil’s uplift deformation. The bending moment of the diaphragm wall was mainly affected near the excavation surface at the bottom of the pit. The closer the support position to the surface, the smaller the effect on the axial force.